An adoption model of electronic government services in Malaysia: electronic labor exchange (ELX) - Zulridah Mohd Noor,; Hasmiah Kasimin,; Aini Aman,; Noraidah Sahari, (Penerbit Universiti Kebangsaan Malaysia, 2011)
The number of Social Networking Sites (SNS) users continues increasing globally. SNS is quickly becoming popular tools for social communication and entertainment. It has now become a trend to share knowledge and the latest news and also interact with each other as well. This paper aims to provide explanation on job searching among employed job seekers through the SNS. 190 survey questionnaires were distributed to employed job seekers who have used online social networking sites via the snowball sampling approach. Data was analysed using Structural Equation Modeling (SEM) technique via the Analysis of Moment Structure (AMOS 16) computer program. SEM is a comprehensive approach to testing hypotheses about relations among observed and latent variables. The proposed model fits the data well. The results demonstrated that that perceived usefulness and perceived enjoyment are positively and significantly related to the behavioural intention to use online SNS as a job search tool, whereas perceived ease of use is not positively and significantly related. The developers of online SNS need to provide additional useful functionalities or tools in the online social networking sites to help users of social networking site with their job searches.